Clinical teaching of law and telepresence: An applied case analysis of the Covid-19 pandemic - Díaz Bravo, Enrique; Astudillo Meza, Constanza (Revista Pedagogía Universitaria y Didáctica del Derecho, 2021)
Clinical teaching of law has been impacted by the Covid-19 pandemic, which has forced the adapting of teaching-learning methodologies by telepresencial means, with the aim of not interrupting the training process. This new stage of clinical teaching of law is not only speculative or laboratory, but all progress has had to be implemented immediately in reality, adapting to the measures that the Judiciary has ordered to give continuity to the administration of justice. In this order of things, the role of clinical education, its evolution, the use of new technologies since the pandemic and the service-learning model are analysed and eventually, a descriptive analysis is made of the results of a questionnaire conducted among students and lecturers of the School of Law of the Universidad Santo Tomás.